La disputa por el discurso del derecho en nuestra América : aportes y tensiones desde los mundos indígenas, tradicionales y quilombolas para la crítica del derecho moderno (Colección Grupos de trabajo, 2022)
The 21st century poses serious challenges and tensions in a world that shows ever more overwhelming violence and misery made as a way of reproducing capital. But in the midst of this maelstrom, the voices of the Indigenous, traditional and Quilombola peoples of the continent are also heard, firm and constant, challenging the arrogant modernity, showing that other worlds are possible, that other worlds, here and now, are being . Their clear voices, through more than five hundred years of tenacious struggle and resistance, mark the passage of a space and a time in which life prevails. That life of all that today trembles before the tyranny of merchandise.